HUBUNGAN ANTARA KELENGKAPAN RESUME MEDIS DENGAN KETEPATAN PEMBAYARAN PASIEN RAWAT INAP OLEH PIHAK ASURANSI KESEHATAN DI RUMAH SAKIT SANTO YUSUP BANDUNG - Imelda Retna Weningsih; Indah Kristina (Lembaga Penerbitan Universitas Esa Unggul, 2013)
AbstractThis journal discusses about the high cost of health care in hospitals has implications for health insurance companies to manage health care costs for its participants as well as possible. Therefore many requirements that must be met by the Hospital in claims expenses to serve inpatients for Medicare participants, one of which is the need to attach a complete medical resume. The purpose of this study to determine the relationship completeness medical resume with the timely payment of health insurance. This study uses cross-sectional study in which the independent variable (Completeness of medical resume) and the dependent variable (accuracy payments) were studied at the same time. Sampling totaling 96 medical records of Medicare inpatient participants, by: determining the sample size (n) equal to the population size (N) divided by one plus the amount of population multiply by the squared level of confidence (1 + N (d2) (Notoatmodjo 2005 hal.92). way measurement with the chi-square test and analysis There is a relationship between the completeness resume with prompt payment of medical inpatients by health insurance at Saint Joseph Hospital Bandung.The results, St. Joseph Hospital has an average per-patient hospitalization the average of 50 patients with BOR 82%, with a bed capacity of 245 TT. Obtained by 74% of medical resume is incomplete, and timeliness of making a new resume reached 14%. And only 3% majority the right Health Insurance pays to St. Joseph Hospital. Gained significance test the relationship between two variables with error level of 5%, chi square = 0.0075 <chi square table = 3.84, then Ho is rejected it means to fail no relationship between the completeness of medical resume with the prompt payment of health insurance. Delays and incomplete medical resume will affect a lot of things, especially health care and sustainability reporting delays. Delays in the payment of health insurance would affect financial stability Saint Joseph Hospital. Results of the interviews can be concluded that there is a possibility of other factors associated with timely payment of among others, billing verification requires manual so long, Hospital Saint Joseph did not use the software provided from the Health Insurance. Conclusion: there is no relationship between the completeness of medical resume with the prompt payment of health insurance. St. Joseph Hospital is advisable to consider that software from the insurance company can be merged with St. Joseph Hospital sosfware in BandungKeywords: resume medis, health assurance, cost of health care